1989
DOI: 10.1111/j.1365-3040.1989.tb01951.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of simulated shadelight and daylight on growth, development and photosynthesis of Pinus radiata, Agathis australis and Dacrydium cupressinum

Abstract: Juvenile seedlings, tnicropropagated plantlets, and adult rooted cuttings of Pinus radiata, together with seedlings of Agathis australis and Dacrvdium cupres.sitium, were grown under either high (670/nnoltn's') or low (200/nnol tn's ') photosynthetic photon flux density (PPFD) and, at low PPFD, under three red:far-red (R/FR) conditions, approxitnately simulating canopy shadelight, daylight and one intertnediate value. In all types of P. radiata, a shade-intolerant species, stetn height and diatneter, stetn and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…Morgan & Smith (1979) found under a relatively high /of 180 //mol m^" s'' that stem extension rate was only slightly affected by R: FR in herbaceous species from closed canopy habitats, but increased markedly in those from open canopy habitats. Warrington et al (1989) observed that for three tree species the responsiveness to R: FR at 200 //mol m"' s"ŵ as inversely related to their shade tolerance. In short term experiments, Impatiens parvifiora (an annual shade tolerator) shows a large increase in stem extension in response to low R: FR under / = 13 //mol m"'^ s^^ (Whitelam & Johnson, 1982).…”
Section: Discussionmentioning
confidence: 92%
“…Morgan & Smith (1979) found under a relatively high /of 180 //mol m^" s'' that stem extension rate was only slightly affected by R: FR in herbaceous species from closed canopy habitats, but increased markedly in those from open canopy habitats. Warrington et al (1989) observed that for three tree species the responsiveness to R: FR at 200 //mol m"' s"ŵ as inversely related to their shade tolerance. In short term experiments, Impatiens parvifiora (an annual shade tolerator) shows a large increase in stem extension in response to low R: FR under / = 13 //mol m"'^ s^^ (Whitelam & Johnson, 1982).…”
Section: Discussionmentioning
confidence: 92%
“…Past research has relied mainly on an approximation of'P, called the v ratio, which is based on the relative amounts of radiation at the peak absorption wavelengths for each form of phytochrome, generally considered to be centered around 660 nm for Pr and 730 nm for Pfr. However, exact values for these peak absorbances can vary, and different researchers have used v to represent a range of ratios (5,7,11,17,20,26). In this paper, v represents the ratio of radiation at 660:730 nm unless otherwise specified.…”
Section: Introductionmentioning
confidence: 99%
“…Lowering of v by either means results in the morphological responses of increased stem elongation (17,18,24,26) and reduced tillering (6,20 x 100 mm) and germinated at 23°C in a multisectioned, controlled-environment growth chamber. All plants in trials 1 to 3 were cv Fielder.…”
mentioning
confidence: 99%
“…Simulated shade, i.e. a low red to far-red (R/FR; 660 nm/730 nm) ratio also elongates pine trees (Warrington et al 1988). Consistently, pine trees produce tall and straight trunks in dense stands, as pine is a shade-avoiding species.…”
Section: Discussionmentioning
confidence: 76%